A Techno-Economic and Socio-Environmental Planning of Wind Farms for Sustainable Development and Transition to a Decarbonized Scenario: Pakistan as a Case Study - Mohammad Uzair Shah (00000329241); Dr Sehar Shakir (USPCAS-E, NUST, Islamabad, 2022)
TH-373
Keywords: MS--ESE Thesis MS Thesis